Late Cretaceous Orbicular Gabbro Cropping Out West Of Elazig (Turkey): Mineralogy, Petrography And Magma Mixing Processes - Ertürk, Mehmet Ali; Sar, Abdullah (International Conference on Scientific and Innovative Studies, 2023)
The lithological units outcropping in the study area, located in the Southeast Anatolian OrogenicBelt, one of the most important parts of the Alpine-Himalayan Orogenic Belt. The study area crops out ina local area within the Hısırık creek in the north of Sarıgül village of Baskil county, which is located in thewest of Elazig province in Southeast Turkey. Elazig Magmatics contains plutonic and sub-volcanic rocks,mainly felsic and mafic compositions. Plutonic rocks with felsic composition include granite, granodiorite,tonalite and quartz monzonites, while sub-volcanic rocks include aplite. Plutonic rocks with maficcomposition are represented by diorite, quartz diorite, gabbro and orbicular gabbro, and sub-volcanic rocksare represented by diabase and diorite porphyries. The orbicular gabbros, which are the subject of the study,macroscopically contain orbicles ranging in size from 1 cm to 15 cm, formed by repetitive concentric circlesof fine and coarse grains. All these orbicles consist of concentric circles that show magmatic textures bothin macro specimens and under the microscope. The orbicles contain olivine, pyroxene amphibole andplagioclase minerals. Olivines are characteristic of their yellow, orange and bluish interference colours andabundant cracked structures. Pyroxenes show one or two planes of cleavage and have high interferencecolours. Plagioclase inclusions point to magma mixing from the sub-ophitic and ophitic textures. Orbicularcircles were formed by the crystallization of basic magma in the form of a circular texture by conventionalrepetition as a result of adding a basic new magma that was later included in the magma chamber duringthe crystallization of basic magma. Mineralogical and petrographic features suggest that the orbiculargabbro is part of mafic igneous enclaves within intrusive mafic rocks.